Materiality in perspective: monuments, object relations, and post-war Berlin. Issue 3 (3rd July 2021) - Schuldenfrei, Robin
Abstract: After the rise of monumental fascist architecture in Europe and the subsequent devastation of the Second World War, architects struggled to come to grips—via writing and design—with what should follow. In the view of architects, artists and cultural critics, monumentality in architecture and urbanism was no longer tenable—tainted as it was by the fascists' use of classicism, monumental scale, and their proposals for extreme perspectival views in large-scale urban planning. Monuments and monumentality were reappraised, to be replaced by objects that were described as 'things that remind', a concept introduced by architectural critic Siegfried Giedion in his ground-breaking essay 'The Need for a New Monumentality' (1944). This essay examines how monumentality was scaled down and revised in post-war period literature and structures—replaced by the idea of small monuments that 'remind', which offered opportunities for inner perspective. By considering Berlin's situated urban materiality and artefacts, including the Berlin Wall, in the light of such manifestos on monuments as Giedion's, this article argues that post-war Berlin building was often at odds with, even against, perspective.